Strengthening Harmony in The Midst of The Rapid Advancement of Information Technology - Siroj, Akhmad Munib (AT-TAJDID: Journal of Islamic Education, 2025)
Indonesia is a pluralistic country in many aspects, including race, ethnicity, regional languages, customs, and religion. To manage this diversity in terms of ethnicity, religion, race, and intergroup relations (SARA), the government frames it within the format of religious harmony, which is defined as "... the state of relationships among religious communities based on tolerance, mutual understanding, mutual respect, appreciation of equality in practicing their religious teachings, and cooperation in social, national, and state life within the Unitary State of the Republic of Indonesia, based on Pancasila and the 1945 Constitution of the Republic of Indonesia." Since religious harmony is a state of being, it is dynamic and influenced by its ability to adapt to social changes in society, including shifts in social structures that encompass patterns of social relationships, social norms, and social roles. Social changes vary not only in terms of degree but also in scale and scope. The development of technology, particularly information technology, has brought significant changes to social behavior. The rapid growth of information technology has altered old social patterns and structures. This change is marked by shifts in interaction patterns, lifestyles, behaviors, perspectives, ways of living, and social orientations. It is worth exploring how we (especially religious leaders) can strive to maintain religious harmony amidst the rapid advancement of information technology. The research method used in this study will be literature research. This literature research will focus on textbook analysis. The research will involve a comprehensive analysis of works discussing the relationship between information technology and religion. The rapid advancement of information and communication technology has accelerated social changes in various fields. An important phenomenon to observe is the fading of values, including religious, cultural, and national values. Society tends to neglect moral values when engaging in social media, focusing instead on what can go viral and generate profit. It is imperative for religious leaders to enter the digital technology realm to carry out their sacred role of delivering messages of morality and goodness, ensuring that religious harmony remains strong. In this context, it is important to involve and provide space for the younger generation to play a role.